A Fast Modeling Technique for the Vertical Train-Track-Bridge Interactions - Hanyun Liu; Zhiwu Yu; Wei Guo (Shock and Vibration)
This paper proposed a fast modeling technique (FMT) for the vertical dynamic analysis of the coupled train-track-bridge (TTB) systems, which combines the train subsystems and track-bridge subsystems by the client-server technique to complete the entire TTB analysis on simplex OpenSees simulation platform. Thus, the FMT could dramatically reduce the time consumed of programming and modeling and significantly reduce the amount of data transmission between subsystems for TTB interaction. Moreover, FMT could take full advantage of OpenSees in nonlinear and seismic analysis. So FMT is a practical and convenient approach to analyze the TTB coupling vibration, and especially it is suitable for the junior researchers of TTB interaction. FMT could improve the modeling efficiency to save time.